Analysing encryption mechanisms and functional safety in a ROS‐based architecture. Issue 2 (31st July 2019) - Larrucea, Xabier; González‐Nalda, Pablo; Etxeberria‐Agiriano, Ismael; Otero, Mari Carmen
Abstract: Robot Operating System (ROS) is a middleware for connecting different components of robots. However, its use is becoming more popular in other domains such as in the automotive sector where initial prototypes have been customized and deployed in cars for demonstrating different functional purposes. Nevertheless, ROS has not been yet tested enough to be used in secure and safety environments. For example, in order to strengthen our ROS architecture, we have encrypted the messages within it. Therefore, this paper analyses the impact of Advanced Encryption Standard (AES) encryption mechanism and the functional safety of our prototype. In this sense, we are considering encrypting messages and we assess the timing constraints, as suggested by the ISO 26262, required for assuring a secure communication between components.